Ethical and practical considerations for mitigating risks to sexual partners during analytical treatment interruptions in HIV cure-related research - Karine Dubé; John Kanazawa; Lynda Dee; Jeff Taylor; Danielle M. Campbell; Brandon Brown; Mallory O. Johnson; Parya Saberi; John A. Sauceda; Jeremy Sugarman; Michael J. Peluso (HIV Research & Clinical Practice, 2021)
Background Background: Analytical treatment interruptions (ATIs) in HIV cure-related research can result in trial participants becoming viremic with HIV, placing HIV-negative sexual partners at elevated risk of acquiring HIV. Objective Objective:Our study aimed to generate ethical and practical considerations for designing and implementing appropriate risk mitigation strategies to reduce unintended HIV transmission events during ATIs. Methods Methods: We conducted 21 in-depth interviews with five types of informants: bioethicists, community members, biomedical HIV cure researchers, socio-behavioral scientists/epidemiologists, and HIV care providers. We used conventional content analysis to analyze the data and generate considerations. Results Results: Key findings include: 1) Ethical permissibility of ATI trials depends on due diligence and informed consent to mitigate risks to participants and their sexual partners; 2) Participants should receive adequate support and/or counseling if they choose to disclose ATI participation to their partners; 3) Measures to protect sexual partners of trial participants from HIV transmission during ATIs should include referral to and/or provision of pre-exposure prophylaxis, as well as other available means of preventing HIV transmission; 4) There is uncertainty regarding the appropriate management of emerging sexually transmitted infections during ATI trials and possible protection measures for multiple and/or anonymous partners of ATI trial participants. Conclusion Conclusion: While there is no way to completely eliminate the risk of HIV transmission to sexual partners during ATIs, HIV cure trialists and sponsors should consider the ethical concerns related to the sexual partners of ATI participants. Doing so is essential to ensuring the welfare of participants, their partners and the trustworthiness of research.